(untitled) - Gottfried, Sandra S.; Sandra S. Gottfried (St. Louis)
This introductory text provides extensive coverage of all aspects of biology, including principles, physiology, genetics, diversity, evolution and ecology. Emphasizing a human focus, the book presents a thorough explanation of ideas and concepts, with a format designed to encourage learning. Information is given on such topics as world population statistics, AIDS, gene therapy, destruction of the rain forest, Alzheimer's disease, the Human Genome Project, the sixth kingdom and the controversy surrounding "Eve". The text focuses on how a biological concept relates to the human body and compares how current biological research is applied to society's problems
Includes bibliographical references and index
Keywords: Biology; Human biology